The Wnt/Ca2+ pathway is involved in interneuronal communication mediated by tunneling nanotubes. (18th October 2019) - Vargas, Jessica Y; Loria, Frida; Wu, Yuan‐Ju; Córdova, Gonzalo; Nonaka, Takashi; Bellow, Sebastien; Syan, Sylvie; Hasegawa, Masato; van Woerden, Geeske M; Trollet, Capucine; Zurzolo, Chiara
Abstract: Tunneling nanotubes (TNTs) are actin‐based transient tubular connections that allow direct communication between distant cells. TNTs play an important role in several physiological (development, immunity, and tissue regeneration) and pathological (cancer, neurodegeneration, and pathogens transmission) processes. Here, we report that the Wnt/Ca 2+ pathway, an intracellular cascade that is involved in actin cytoskeleton remodeling, has a role in TNT formation and TNT‐mediated transfer of cargoes. Specifically, we found that Ca 2+ /calmodulin‐dependent protein kinase II (CaMKII), a transducer of the Wnt/Ca 2+ pathway, regulates TNTs in a neuronal cell line and in primary neurons. We identified the β isoform of CaMKII as a key molecule in modulating TNT formation and transfer, showing that this depends on the actin‐binding activity of the protein. Finally, we found that the transfer of vesicles and aggregated α‐synuclein between primary neurons can be regulated by the activation of the Wnt/Ca 2+ pathway. Our findings suggest that Wnt/Ca 2+ pathway could be a novel promising target for therapies designed to impair TNT‐mediated propagation of pathogens. Synopsis: Tunneling nanotubes (TNTs) are actin‐based thin channels that connect distant cells, allowing the direct transfer of cellular materials, including pathogenic molecules. Whether these structures are formed in neurons and how they are regulated, is not clear yet. Here, we investigated the role of the Wnt/Ca 2+ pathway on the formation and stabilization of TNTs. Activation of the Wnt/Ca 2+ pathway modulates the formation of TNTs through the action of the β isoform of Ca 2+ /calmodulin‐dependent protein kinase II (βCaMKII). βCaMKII in its unphosphorylated state binds to F‐actin inside TNTs and likely stabilizes the structure. Primary neurons form communicating TNT‐like structures in vitro . The transfer of aggregated α‐synuclein in primary neurons can be modulated by the Wnt/Ca 2+ pathway. Abstract : Wnt‐mediated activation of actin‐binding CaMKII regulates tunneling nanotube formation and transfer of vesicles and pathological protein aggregates between neurons.